PENERAPAN MODEL STUDENT TEAMS ACHIEVEMENT DIVISION DAN MEDIA GAMBAR WAYANG UNTUK MENINGKATKAN KEMAMPUAN MEMBACA AKSARA JAWA - Ahmad Dwi Romadhoni; Atikah Anindyarini; Astiana Ajeng Rahadini (Universitas Sebelas Maret, 2023)
The author made this study with the aim of explaining a learning process using the student teams achievement division method and wayang image media. This research is subject to students in class VIII A of SMP Negeri 1 Widodaren. This research was applied in 2 cycles, where each cycle of application consisted of action planning, action implementation, observation or observation, analysis and reflection. The technique used in the collection is document study through tests in cycle 1 and cycle 2. The results of this study can be seen that the application of the student teams achievement division method and wayang image media to class VIII A students of SMP Negeri 1 Widodaren in the 2018/2019 academic year can improve students' ability to read Javanese script in 2 cycles. In the pre-action stage, students who achieved 38% completeness increased in cycle 1 to 51.61% in cycle 2 increased to 87.1%. This study has results that can be used as a reference for teachers to use the student teams achievement division method and puppet image media in Javanese language learning in class VIII to improve reading skills in Javanese script.